A Systematic Review of Procedural Complications from Transforaminal Lumbar Puncture for Intrathecal Nusinersen Administration in Patients with Spinal Muscular Atrophy - Grayev, A.; Schoepp, M.; Kuner, A. (American Journal of Neuroradiology, 2021)
BACKGROUND: Spinal muscular atrophy is a progressive neurodegenerative disorder that can be treated with intrathecal antisense oligonucleotide therapy (nusinersen). However, administration is often complicated by posterior spinal fusion and neuromuscular scoliosis, necessitating a transforaminal approach.PURPOSE: To assess the safety profile of the transforaminal approach for intrathecal access.DATA SOURCES: Searches of the PubMed, Web of Science, and SCOPUS databases.STUDY SELECTION: Thirteen articles were selected based on inclusion of transforaminal access and appropriate clinical information about the procedure.DATA ANALYSIS: Complications were taken from the included articles and aggregated based on Cardiovascular and Interventional Radiological Society of Europe scale adverse event grading.DATA SYNTHESIS: Total number of complications and grade of complications were analyzed, by year and in total.LIMITATIONS: Selection bias in publication, small patient population size, and variability of the procedure limits the available data.CONCLUSIONS: Transforaminal approach is a safe alternative for intrathecal access in patients with spinal muscular atrophy and may be applicable to a larger patient population.CBCTconebeam CTCIRSECardiovascular and Interventional Radiological Society of EuropeSMAspinal muscular atrophy